O pensamento litúrgico de Edith Stein: contexto conceito contribuição - Dalabeneta, Eduardo (2013)
At the advent of 15th anniversary commemoration of canonization of Saint Theresa Benedicta of the Cross, Edith Stein, (22.05.1997 - 22.05.2013), there is an urgent need to systematize her liturgical thoughts, at the postgraduate stricto sensu level. The synthesis of this Carmelite theologian s thought is focused on her affirmation that the liturgy is the Church s prayer, of the living Christ. From this starting point, the ways are made towards a conclusion that to participate, to live, to celebrate and to be in union with the filial prayer of Jesus of Nazareth, the Christ, nucleus and the vivificant principle of the liturgical rites of the Christian community, means to restore and to bring to epiphany the dignity of son and daughters of God. It is to reestablish and to teach how to live fraternal relationships and the freedom subjected to it (humanization-glorification-divinization)